ROLE OF CALCIUM SUPPLEMENT AND EXERCISE IN MANAGEMENT OF WOMEN HAVING OSTEOPENIA AND OSTEOPOROSIS: Role of Calcium Supplement - Anjum, Nagin; Dar, Nasser Rashid (Pakistan Armed Forces Medical Journal, 2008)
Objective: To measure the effects of calcium supplements and exercise on bone mineral density in women between 35-70 years. Design: Quasi experimental study. Place and Duration of Study: The study was conducted in the department of gynecology Combined Military Hospital Abbotabad, from July 2004 to June 2006. Patients and Methods: Based upon bone mineral densities T score 39 patients were assigned to group A (osteopenic) and 20 patients to group B (osteoprotic). Both groups were subdivided into I and II groups. The cases in group-IA and group-IIA were given calcium Ossonate 800 mg in two divided doses. Whereas, the cases in group-IB and group-IIB were advised to take dietary calcium in the form of two glasses milk (300 mg calcium/glass) and one hour brisk walk daily. Results: Better improvement in bone mass density was noted in group I-B patients as compared to other groups. Conclusion: In osteopenia a combination of dietary supplementation and brisk walk is beneficial in maintaining or improving bone mineral density. In osteoporosis, the more severe form of the disease, simple calcium supplements or dietary calcium supplementation with exercise are not helpful.